Assessment of Medium-Term National Action Agenda for Productivity (MNAAP) for the Agriculture Sector - Cristina C. David; Arlene B. Inocencio (Philippine Institute for Development Studies (PIDS), 2001)
To attain productivity growth it is necessary to have proper diagnosis and analysis of the sources and causes of low or stagnant agricultural productivity. This paper highlights the major issues in agriculture, examines the MNAAP agenda on productivity and identify the remaining gaps. The paper shows how government policy and institutional interventions have contributed to the erosion of the country's competitive advantage and hence to the poor performance of the agricultural sector since the 1980's. These interventions include the price and market policy interventions, policies on property rights and the public expenditure allocations which have hindered the achievement of a higher productivity in the sector. The examination of the MNAAP 2000-2004 goals, strategies, and activities shows that as government draws a map for agriculture productivity growth, no clear steps and actions are geared towards addressing the major policy constraints besetting the sector which can be considered as a prerequisite to attainment of productivity growth.
Keywords: 330; property rights; agricultural productivity; market policy intervention; public expenditure allocation; Haushaltsplanung; Produktivität; Landwirtschaft; Philippinen